A study of cartoon character for food and children story book / Dyana Hazirah Kamaruddin - Kamaruddin, Dyana Hazirah (2019)
Food character is one of the best promising strategies to increase children’s preference, choice, and intake of healthy food compared to not using characters for branding. The qualitative case studies focused on food character in animation and story book for children book. Essentially, the role of food cartoon characters in influencing children's food choices because the effect is very clear when sweet or salty snacks labelled by a character preferably compete with a better choice labelled by a character or an unknown character. The studies explore how food cartoon character as alternative to persuade children by choosing food they do not like. In this assignment, study about food character for children. The study utilized observations the ideal food features are used as a cartoon character to attract children to eat healthy food, advantages and disadvantages food character as a medium to attract children. Data was gathered from many sources: observations of studies while work in class, several books and article from internet.